Comparison of the Anthropometric Indices to Identify Prehypertension Among Male Medical Students (Jurnal Ilmu Kesehatan Masyarakat, 2023)
The state of prehypertension that is often neglected in young adults is not inferior to hypertension in contributing to a higher risk of cardiovascular diseases. Several simple anthropometric indices may be used as prehypertension prognostic tools, including Body Mass Index (BMI), Body Shape Index (ABSI), Waist Circumference (WC), Weight to Height Ratio (WHtr), and Body Roundness Index (BRI). This study aimed to compare several anthropometric examinations for detecting prehypertension in male medical students. The cross-sectional study design was conducted on 107 male medical students. Direct measurements of the respondents were carried out with blood pressure data collection and anthropometric examination. The area under the receiver-operating characteristic curve (AROC) analysis with a 95% confidence interval (CI) was used to assess all anthropometric measures’ discriminatory power to assess the risk of prehypertension in the participants. Participants with prehypertension were relatively older and had less active physical activity than normotensive (p<0.05). The mean BMI, BRI, WC, and WHtR were significantly higher in the prehypertensive group than in the normotensive group. However, ABSI was not showing any relationship with blood pressure. The process with 95% CI of blood pressure classification related to anthropometric measures indicates that BMI showed the highest AROC values for the prehypertensive state (AROC: 0.73, 95% CI: 0.63–0.82), and WC had the lowest AROCs (AROC: 0.63, 95% CI: 0.52–0.63). BMI, BRI, WC, and WHtr may be applied as prognostic assessments for prehypertension states in young adult males.